2021
DOI: 10.1080/15427528.2021.1943732
|View full text |Cite
|
Sign up to set email alerts
|

Soybean seed weight responds to increases in assimilate supply during late seed-fill phase

Abstract: The understanding of source-sink dynamics during reproductive stages is essential to increase crop productivity and to describe yield component determination in eco-physiological models. Previous studies in soybean (Glycine max [L.] Merr.) evaluated the effect of changes in assimilate supply from the beginning of rapid seed growth but not at different times during the seed-filling phase or at the single-pod level. Two source-sink manipulation experiments were conducted in the greenhouse to quantify the effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The effect of the dose orientation treatment of gamma rays. It can also be concluded that the higher the radiation dose given, the plant's ability to produce leaves is also reduced [6]. As for the 0 Gy or control doses, 200 Gy, 300 Gy, 400 Gy had a lower average number of leaves.…”
Section: Number Of Leavesmentioning
confidence: 93%
See 1 more Smart Citation
“…The effect of the dose orientation treatment of gamma rays. It can also be concluded that the higher the radiation dose given, the plant's ability to produce leaves is also reduced [6]. As for the 0 Gy or control doses, 200 Gy, 300 Gy, 400 Gy had a lower average number of leaves.…”
Section: Number Of Leavesmentioning
confidence: 93%
“…Expansion of the planting area can be achieved by utilizing the unproductive lands, sub-optimal lands and shaded lands [5]. In line with these problems, planting shade-tolerant soybeans as intercrops is considered as one of the efforts that can be taken to increase land productivity [6]. while, increasing the production of broad meaning, including by using high-yielding varieties assembled through plant breeding programs.…”
Section: Introductionmentioning
confidence: 99%
“…In all of the previous field studies in soybean, source and sink were manipulated across the entire pod growth period. A recent study in a greenhouse setting [34] employing increased assimilate supply during different seed filling stages found that soybean seed size responds to an increase in assimilate supply until the late seed filling phase. This result suggests that seed size in soybean is determined during the late seed filling stage.…”
Section: Introductionmentioning
confidence: 99%
“…In conditions of unfavourable day length, insufficient flow of assimilation products to growth points with a lower intensity of their accumulation and outflow leads to later formation of generative organs (Hider & Zhmurko, 2020). It has also been shown that in the field, the final weight of the seed can reach 68% to 85% of its potential, depending on environmental conditions (Chiluwal et al, 2021). The starch content of the seed is a decisive factor affecting the quality of soybean food products.…”
Section: Introductionmentioning
confidence: 99%